The Impact of Hotel and Restaurant Tax Contributions to Local Revenue on Kabupaten Garut in 2017-2021: (A Case Study of Local Revemue Service in Kabupaten Garut) - Eka Meitasari, Clarissa; Indrawati, Lili; Putra, Sugih Sutrisno (Indonesian Accounting Research Journal, 2024)
The purpose of this study is to determine how hotel and restaurant taxes affect Kabupaten Garut's regional original income. This kind of study adopts a descriptive methodology and quantitative techniques. Secondary data from. reports on the collection of hotel and restaurant taxes, and local revenue for the 2017–2021 fiscal year is the source of the information used. With the use of SPSS version 26 software, the analysis approach makes use of the traditional assumption..test, multiple regression analysis, and hypothesis..testing. The Regional Original Income is unaffected in part by the Hotel Tax Contribution. However, the simultaneous contribution of the hotel and restaurant taxes has a considerable impact on regional original income. Hotel and.restaurant taxes had an impact on municipal revenue to the extent of 13.7 percent, with the other factors not covered in this study accounting for the remaining 86.3 percent.